The Contribution of Social Sciences in Strengthening the Character Education of Elementary School Students - Eko Mafrudin (Balai Publikasi Indonesia, 2023)
One of the objectives of social studies education is to form good citizens. To be a good citizen, every student must have good character as well. This implies that social studies education must be able to contribute to shaping student character. In this study, we will review the role of social studies education in strengthening character education in elementary schools. This research uses a library research approach. Sources of data are obtained from research results that have been published in scientific journals, books, and legislation related to the education system. The results of the study show that social studies education has a very important role in strengthening character education in elementary schools. The role of Social Studies Education in character building is to contribute in the form of basic values, concepts, and rules in shaping student behavior both in the school environment and in the community environment.